Visualization of Right Adrenal Vein in Non‐Contrast‐Enhanced MDCT and Its Guiding Role for Right Adrenal Venous Sampling - Hong‐liang Xiong; Li Du; Jiao Yang; Wei‐Tong Hu; Jia‐Bing Huang; Yun‐De Li; Xi Chen; Yi‐Fei Dong (The Journal of Clinical Hypertension)
ABSTRACT This study aimed to evaluate the visualization of right adrenal vein (RAV) in non‐contrast‐enhanced multi‐detector computed tomography (MDCT) and its guiding role for right adrenal venous sampling (AVS) in patients with primary aldosteronism (PA). A total of 237 patients diagnosed with PA who underwent successful AVS procedures from January 2020 to March 2021 were retrospectively analyzed. The non‐contrast‐enhanced MDCT image features of RAV included the degree of visualization and the position of RAV orifice. Subsequently, the concordance degree between RAV in non‐contrast‐enhanced MDCT and AVS images was calculated to evaluate its guiding effect for right AVS. The visualization rate of RAV in non‐contrast‐enhanced MDCT was 81.9% (n = 194), with 73.7% (n = 143) clearly displayed and 26.3% (n = 51) generally displayed. In 6.2% (n = 12) of patients who can display RAV, RAV formed a common trunk with the accessory hepatic vein and then merged into the inferior vena cava. Non‐contrast‐enhanced MDCT revealed that RAV orifice was located between the 10th thoracic vertebra (T10) and the 1st lumbar vertebra (L1), with 85.1% (n = 165) located from the lower 1/3 of T11 to the lower 1/3 of T12. The concordance of imaging anatomy of RAV between non‐contrast‐enhanced MDCT and AVS image was found to be at a high rate of 94.3% (n = 183). Non‐contrast‐enhanced MDCT provides excellent visualization of RAV and clearly depicts its anatomical characteristics. Furthermore, RAV images obtained from non‐contrast‐enhanced MDCT are highly consistent with those from AVS, indicating that interpretation of non‐contrast‐enhanced MDCT before AVS can reduce the failure rate of RAV cannulation.